Role of biomarkers of myocardial injury and inflammation in predicting ischemia-reperfusion injury in patients with ST-segment elevation acute coronary syndrome undergoing endovascular revascularization - T. V. Rusak; L. G. Gelis; E. A. Medvedeva; I. I. Russkikh; N. A. Shibeko; S. A. Kurganovich; T. T. Gevorkyan (Российский кардиологический журнал)
Aim. To evaluate the informative value of biomarkers (cardiac troponin l (cTnl), high-sensitivity C-reactive protein (hsCRP), N-terminal pro-brain natriuretic peptide (NTproBNP), stimulating growth factor (ST2)) as laboratory markers of myocardial ischemia-reperfusion injury in patients with ST-segment elevation acute coronary syndrome (STEACS) undergoing endovascular revascularization.Material and methods. The study included 115 patients with STEACS who underwent endovascular myocardial revascularization. To identify the informative value of biomarkers, the levels of cTnl, NTproBNP, hsCRP, sST2 were analyzed at baseline, as well as after reperfusion therapy on the 2nd (cTnl) and 5th (sST2, hsCRP, NTproBNP) days. Contrast-enhanced cardiac magnetic resonance imaging was performed 5 days after endovascular intervention.Results. Microvascular obstruction was detected in 54 patients (47%), of which 24 (44%) patients had a combination of microvascular obstruction and myocardial hemorrhage. ln 61 cases (53%), no microvascular damage was registered. lt was found that with an increase in the threshold initial NTproBNP levels >590 pg/ml, the odds ratio (OR) of myocardial reperfusion injury was 12,2 (95% confidence interval (CI), 4,81-30,92, p<0,001). In addition, we analyzed biomarker levels in the early period after myocardial infarction, at which threshold values of reperfusion injury parameters were established as follows: for cTnI >8,1 ng/ml, OR=7,17 (95% CI, 3,11-16,53, p=0,001); for hsCRP >14 mg/L, OR=12,71 (95% CI, 5,03-32,08, p=0,001); for NTproBNP >334 pg/ml, OR=11,8 (95% CI, 4,88-28,59, p=0,001); for sST2 >41 ng/ml, OR=7,17 (95% CI, 3,11-16,53, p=0,001). According to multivariate analysis, predictors of microvascular injury were the initial NTproBNP values, as well as the cTnI, hsCRP, and sST2 values in the early postinfarction period (sensitivity — 89,5%, specificity — 83,3%).Conclusion. Thus, the initial NTproBNP, as well as cTnI, hsCRP, sST2 values after percutaneous coronary intervention are more informative for assessing the risk of microvascular damage.